A review of the use of high flow nasal cannula oxygen therapy in hospitalized children at a regional hospital in the Cape Town Metro, South Africa - Hoffman, Elizabeth (Department of Paediatrics and Child Health, 2019)
Background: High-flow nasal cannula oxygen (HFNC) is a non-invasive alternative to nasal continuous positive pressure oxygen (CPAP) therapy for infants and children requiring respiratory support. There is a paucity of literature to support its use in children, with no published data from sub-Saharan Africa. Objective: To describe the outcomes and adverse events of HFNC in the first year of its use in a level two (L2) general paediatric ward, compared with outcomes of a historical cohort when this intervention was unavailable. Methods: This retrospective descriptive study included children aged <13 years who received HFNC in the first 12 months after its introduction (HFNC-availability group; n=66). Demographic data, clinical characteristics, and outcomes (death, treatment failure, length of HFNC, and HFNC-related adverse events) were assessed. A comparative description of children that required transfer to level 3 (L3) for respiratory support (more than available standard low-flow oxygen) in the 12-month period prior to HFNC availability (pre-HFNC group; n=54) was performed and outcomes were compared using standard descriptive and comparative statistics. Results: The median age of the cohort was 5 months (interquartile range [IQR] 1.9– 14.6). Sixteen children (13.3%) were malnourished, 10 (8%) were HIV infected, and 30 (25%) were ex-premature infants. The most common diagnoses were pneumonia, bronchiolitis, and asthma. Asthma, anaemia, and cardiac abnormalities were the most prevalent underlying co-morbidities. Two children died in each group. All 54 children in the pre-HFNC group were transferred to L3; 38 (70.4%) needed CPAP or invasive ventilation. In the HFNC-availability period, 85 children were assessed as needing more than standard low-flow oxygen therapy: 19 were immediately transferred to L3 where 17 (89.4%) received CPAP or invasive ventilation; 66 received HFNC at L2, 16 (24.2%) of these children required transfer to L3 for CPAP or invasive ventilation. The median duration of HFNC was 46.3 h (IQR 19.5–93.5) overall, and was 12 h (IQR 4-28) and 58.5 h (IQR 39.5–106) for those who failed or were successfully managed on HFNC, respectively. No HFNCrelated serious adverse events were recorded at L2. Conclusion: HFNC is a safe, effective, feasible option for non-invasive ventilation of children with respiratory illnesses in a resource-limited L2 setting. A greater proportion of children admitted with lower respiratory tract infections required support in the HFNC-availability group, but the intervention reduced the bed- pressure on L3. Improved identification of HFNC failures and better adherence to the protocol is needed at L2.